ISLAMIC BANKING STRATEGY IN FACING THE NEW NORMAL ERA DURING THE COVID 19 - Mutiah Khaira Sihotang; Hasanah Hasanah (Proceeding International Seminar of Islamic Studies, 2021)
Covid 19 has impact on the world economy without exception for Indonesia. Banks have the most important role in the economy and have also felt a huge impact with the corona virus that broke out at the end of 2019. This caused the economic sector, including banking, to think about how to survive the conditions of Covid 19 which were hitting. Islamic banking establishes new policies in order to continue to exist in this very worrying condition. This type of research is a library research with qualitative data analysis. The results showed that there was a decline in several aspects experienced by Islamic banking, including an increase in the NPF, decrease in customers applying for financing and decrease in demand for Islamic bank products. For this reason, Islamic banks decided to establish a new strategy in facing the new normal during the pandemic. Several strategies that must be carried out in order to survive in this new normal era include restructuring financing, spurring growth by selecting businesses that are still developing, digitizing banking services, providing assistance to UMKM players, and making innovations both in terms of services and products.Keywords: Islamic banking strategy, new normal era, covid 19.